Enabling Action: Reflections upon Inclusive Participatory Research on Health with Women with Disabilities in the Philippines. Issue 3 (20th October 2020) - Vaughan, Cathy; Gill‐Atkinson, Liz; Devine, Alexandra; Zayas, Jerome; Ignacio, Raquel; Garcia, Joy; Bisda, Krissy; Salgado, Joy; Marco, M. Jesusa
Abstract: People with disabilities experience health disparities arising from social, environmental, and system‐level factors. Evidence from a range of settings suggests women with disabilities have reduced access to health information and experience barriers to screening, prevention, and care services. This results in greater unmet health needs, particularly in relation to sexual and reproductive health. Women with disabilities are also more likely to experience physical and sexual violence than women without disabilities, further undermining their health. Community‐based participatory research (CBPR) can generate knowledge and underpin action to address such health disparities and promote health equity. However, the potential and challenges of disability inclusion in CBPR, particularly in contexts of poverty and structural inequality such as those found in low‐ and middle‐income countries, are not well documented. In this paper, we reflect on our experience of implementing and evaluating W‐DARE, a three‐year program of disability‐inclusive CBPR aiming to increase access to sexual and reproductive health and violence‐response services for women with disabilities in the Philippines. We discuss strategies for increasing disability inclusion in research and use a framework of reflexive solidarity to consider the uneven distribution of the benefits, costs, and responsibilities for action arising from the W‐DARE program. Highlights: Disability inclusive community‐based participatory research can address health inequalities. Inclusion increases quality and impact of research, but has material, personal and political costs. The costs of inclusive research are disproportionately born by co‐researchers with disabilities. Participatory research can contribute to new solidarities for sustained health‐promoting action.